Effect of ultrasonic irradiation on morphology and polymorphic transformation of glycine - SAYAN, PERVİZ; POLAT, SEVGİ (ELSEVIER SCIENCE BV, 2018)
The polymorphic phase transformation of 13-glycine to a-glycine was analyzed in the absence and presence of three different intensities of ultrasonic irradiation in a batch system at 25 degrees C. The experiments were performed to explore the effects of ultrasonic irradiation and its intensity on phase transformation time, morphology, storage stability, and filtration characteristics. The crystals obtained with and without ultrasound were characterized by X-ray diffraction (XRD). The XRD results showed that the ultrasound tended to reduce the transformation time. According to the scanning electron microscopy (SEM) images, the ultrasound had a significant effect on the crystal morphology. The highest ultrasound power applied yielded more rounded crystals compared to the crystals prepared in the absence of ultrasound. In addition to SEM analysis, detailed crystal shape analysis was performed and shape factors, namely the circularity, elongation, and convexity values, were determined quantitatively to get more information about the morphological changes related to the variations in the size and shape of the end products. From the morphological point of view, the circularity values of the crystals obtained under ultrasound were higher but the elongation values were smaller compared to the crystals obtained in the absence of ultrasound. It was also found that higher ultrasound decreased the length and width of the crystals, and the application of ultrasound increased the aspect ratio value from 0.483 to 0.657.
Keywords: Ultrasonic irradiation; Polymorphs; Shape parameters; Transformation; Glycine; ANTI-SOLVENT CRYSTALLIZATION; P-AMINOBENZOIC ACID; NUCLEATION; CRYSTAL; GROWTH